GABA bouton subpopulations in the human dentate gyrus are differentially altered in mesial temporal lobe epilepsy - Alhourani, Ahmad (J Neurophysiol, 2020)
Medically intractable temporal lobe epilepsy is a devastating disease, for which surgical removal of the seizure onset zone is the only known cure. Multiple studies have found evidence of abnormal dentate gyrus network circuitry in human mesial temporal lobe epilepsy (MTLE). Principal neurons within the dentate gyrus gate entorhinal input into the hippocampus, providing a critical step in information processing. Crucial to that role are GABA-expressing neurons, particularly parvalbumin (PV)-expressing basket cells (PVBCs) and chandelier cells (PVChCs), which provide strong, temporally coordinated inhibitory signals. Alterations in PVBC and PVChC boutons have been described in epilepsy, but the value of these studies has been limited due to methodological hurdles associated with studying human tissue. We developed a multilabel immunofluorescence confocal microscopy and a custom segmentation algorithm to quantitatively assess PVBC and PVChC bouton densities and to infer relative synaptic protein content in the human dentate gyrus. Using en bloc specimens from MTLE subjects with and without hippocampal sclerosis, paired with nonepileptic controls, we demonstrate the utility of this approach for detecting cell-type specific synaptic alterations. Specifically, we found increased density of PVBC boutons, while PVChC boutons decreased significantly in the dentate granule cell layer of subjects with hippocampal sclerosis compared with matched controls. In contrast, bouton densities for either PV-positive cell type did not differ between epileptic subjects without sclerosis and matched controls. These results may explain conflicting findings from previous studies that have reported both preserved and decreased PV bouton densities and establish a new standard for quantitative assessment of interneuron boutons in epilepsy. NEW & NOTEWORTHY A state-of-the-art, multilabel immunofluorescence confocal microscopy and custom segmentation algorithm technique, developed previously for studying synapses in the human prefrontal cortex, was modified to study the hippocampal dentate gyrus in specimens surgically removed from patients with temporal lobe epilepsy. The authors discovered that chandelier and basket cell boutons in the human dentate gyrus are differentially altered in mesial temporal lobe epilepsy.